Uluru Statement from the Heart: Australian Public Law Pluralism - Dani Larkin; Kate Galloway (Bond Law Review)
It is now over a year since the declaration of the Uluru Statement From the Heart (the ‘Uluru Statement’). Following an exhaustive series of dialogues with Aboriginal and Torres Strait Islander community throughout Australia, the Uluru Statement offers an Indigenous-led legal, political, and cultural solution for bringing together Indigenous and non-Indigenous Australians within our system of governance. Its three pillars are Voice, treaty, and truth-telling. In this comment we provide an overview of the Uluru Statement and its importance in Australia’s legal landscape. We do so as a background to our key contention that the Uluru Statement is a central pillar in a truly pluralistic Australian public law. Regardless of its political reception — at the time of writing the Australian government has rejected it out of hand — the Uluru Statement represents a milestone of Australian law offering a vital opportunity to integrate Indigenous law into an otherwise settler legal system.